Terrorism in Media Political Discourse: from Metaphorical Expressions to Cognitive Models - Arcimavičienė, Liudmila (Verbum, 2010)
This study aims at analysing metaphorical expressions and reconstructing TERRORISM metaphors in British and Lithuanian media political discourse in the theoretical framework of cognitive linguistics and political philosophy (Lakoff and Johnson 1999, Johnson 1993, Elshtain 2004, Fairclough 2001, Spencer 2006, Turner 2002, etc.). For that purpose, thirty-six analytical articles, searched by the key word ‘terrorism (En.) / terorizmas (Lith.)’ were collected from the online archives of The Economist and www.politika.lt. The method applied to investigate the collected data is that of qualitative analysis in the theoretical framework of cognitive linguistics and conceptual metaphor theory (Чудинов 2001, Fauconnier and Turner 2002, Kövecses 2002, Lakoff 2001, 2002, etc.). The findings reveal that despite different time patterns of the collected data sources (i. e. English 2010; Lithuanian 2005, 2006, 2007, 2008) the analogous metaphors of WAR, CRIME and HEALTH have been reconstructed. Their analysis shows the prevalence of pragmatic political morality to TERRORISM governed by the concepts of STRENGTH, ORDER and CONTROL. Even more, their use spreads fear of terrorism by exploiting the image of terrifying war scenes, serious criminal activities and the deadly virus rapidly contaminating social order.
Keywords: media political discourse; terrorism; metaphorical linguistic expressions; conceptual metaphor; pragmatic politics